ANALISIS DAMPAK LINGKUNGAN : STRATEGI MENUJU PEMBANGUNAN BERPUSAT PADA RAKYAT DAN PDRB HIJAU - Lasmiatun - (DHARMA EKONOMI, 2011)
ABSTRACTDevelopment is growth plus change, which is a combination of various processes of economic, social and political, to achieve a better life. There are 3 (three) domains of biological diversity in development, namely : the economic domain, social domain, domain and ecology / biodiversity. Development must put people at the center of attention and the development process must benefit all parties.Economic growth, equity and poverty eradication are the main problems faced by every development effort aimed at improving the welfare of society. Green Gross Regional Domestic Product (GRDP) is the result obtained by an area taking into account the surrounding environment (environmentally sound). Thus, not only on economic but also technical calculations concerning the management of natural resources. Green GRDP is expected to play a role in encouraging fiscal policies that favor conservation of natural resources. So that the necessary regulations governing the management of natural resources so that sustainability can be maintained. Keywords: Green GRDP, people-centered development, biological diversity.